IMMUNOINFLAMMATORY RESPONSE TO RTMS IN FACIAL NERVE NEUROPATHY: DYNAMICS OF IL-6, IL-10 AND C-REACTIVE PROTEIN - Khodjiyeva Dilbar Tadjiyevna,; Akhmedova Dilafruz Bahodirovna,; h Bukhara State Medical Institute, (TADQIQOTLAR, 2026)
Abstract Objective:  To  analyze  the  immunobiochemical  response  to  different  rTMS frequencies in facial nerve neuropathy. Methods: IL-6, IL-10 and C-reactive protein (CRP) were compared before and after treatment in patients receiving 1 Hz rTMS, 10 Hz rTMS or conventional therapy. Results: The strongest decrease in IL-6 and CRP and the most pronounced increase in IL-10 occurred in the 10 Hz group. Conclusion: High-frequency rTMS appears to modulate the inflammatory–regenerative balance in facial nerve neuropathy and may be useful when inflammatory activity is clinically relevant.